Part Typewriter, Part Divination: A Black Feminist Approach to Black Digital Archives and Preserving the Papers of the Campaign to Bring Mumia Home. (14th October 2022) - Millward, Jessica; Willoughby-Herard, Tiffany; Carter, LaShonda; Tribbett, Krystal; Turenne, Ella
Abstract : Black Digital Humanities in the hands of Black Feminist and Black Women's Studies scholars enables historiography and open access pedagogy about Black liberation thinkers in the tradition of the Black Studies Movement.1 Furthermore it is a subversive model of archiving which produces a counter-narrative to traditional and canonical ways of thinking, producing, and storing work that is coming out of Black liberatory movements, praxis, creative social visions, and knowledge production. For our purposes we describe this as the myriad valences of Blackness experienced, encompassed, and reproduced. This paper theorizes the ways in which Black Digital Humanities can be used to preserve historical documents that would otherwise be repressed and erased in the evolving world of online databases, open access and for-profit library packages. It examines these questions by discussing the creation of the Activist Studio West (ASW) and its efforts to preserve the history of The Campaign to Bring Mumia home. We deploy Black Feminist praxis through collaborative interventions into historiography as a key feature of political consciousness raising. The stakes of this article (and archive) call into question the fundamentals of digital humanities and what it means to develop a digital repository to document Black Radical Political movements as Black Feminists. Research team members, historian Jessica Millward, political scientist Tiffany Willoughby-Herard, Black cultural studies scholar LaShonda Carter, visual culture scholar Ella Turenne, and ethnic studies archivist Krystal Tribbett prioritized introducing students to the major scholarship on creating community based archives, the ethical concerns around this particular type of Black Radical archive, and the political ethos involved in initiating an archive around a figure that has been consistently threatened by state sanctioned historical record. As a research methods driven paper we have focused on concept and theory-building toward curriculum development.